ISOLATION AND IDENTIFICATION OF BACTERIA PRODUCING PIGMENTS FROM GARBAGE DUMPED GROUND SOIL (International Journal of Food and Nutritional Sciences, 2022)
In this present study the pigment producing microorganisms were isolated from garbage dumping ground and identified its morphological and biochemical characterization. The bacterial isolates were pseudomonas sp, serratia sp, and staphylococcus sp. These isolates were produced the coloured pigments. In this study much focus is on the production of natural pigment from bacterias. The pigment producing bacteria were isolated from garbage dumping ground and the isolate are Serratia sp, Pseudomonas sp, Staphylococcus sp. This isolates was produce various coloured pigments such as green, yellow, orange. These pigments were extracted from the broth by centrifugation method. These extracted pigments shows antimicrobial activity against human pathogen such as E.coli. Then these extracted pigments were applied on the textile industry. The use of synthetic dyes in these industry cause problems in environment such as toxicities. The synthetic dyes are not environment friendly. The natural colours are more advantage than synthetic colours, they have antibacterial, antifungal, viricidal, anti-oxidant, anticancer activities etc.